Peran Badan Usaha Milik Desa (Bumdes) Sebagai Upaya Pengembangan Ekonomi Masyarakat Desa Pejanggik - Salihin, Agus (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2021)
The purpose of this study is to determine the role of Village-Owned Enterprises as an effort to develop the economy of the Pejanggik Village community. This type of research is descriptive qualitative research. The resourch research data consists of BUMDes managers and communities who receive business development assistance. The data collection techniques consist of observation, interview and documentation techniques. While the data analysis technique, the researcher used the analysis method by Milles and Hubarman which included data presentation, data reduction and conclusion drawing. The results of the study can be explained that the role of BUMDes Desa Pejanggik is not going well and has not been able to significantly improve the economy of the Pejanggik Village community. This is due to the lack of available capital, public awareness and inadequate human resources.